INTERNATIONAL EXPERIENCE OF CONSTRUCTING TRANSPORT AND LOGISTICS CENTERS AND PROSPECTS FOR UKRAINE - Kolesnikov, V.P.; Chupryna, N.N.; Garkysha, V.V.; Kuchkova, O.V. (Systems and Technologies, 2019)
Current trends in international trade are related to the establishment and distribution of transport and logistics centers. Foreign practice demonstrates that the latter is the most successful form of organization of international freight. Such centers make it possible to combine transport types and offer a wide range of related services. The article describes the European experience in the development of transport and logistics centers in order to identify opportunities for its adaptation in Ukraine. The experience of the countries of Western Europe testifies to the huge role of transport and logistics centers. The peculiarities of the functioning of international transport and logistics centers of such countries as Germany, Italy, France, China, Japan and others are investigated. The peculiarities of the functioning of logistics centers in Western Europe, Russia and China are revealed. It is revealed that in the countries of the European Union large transport and logistics centers are created with the support of the state. All transport and logistics centers in the European Union are in accordance with the conventional structure, and the presence or absence of individual elements depends on the size of the transport and logistics center, its location and purpose of operation. The research revealed the main obstacles to the development of the domestic logistics market. The prospects of creation of transport and logistics centers not only of regional but also international importance in Ukraine are outlined. For successful operation of transport and logistics centers there is a lack of: developed transport infrastructure and integration of transport enterprises; cooperation between state bodies of executive power; diversification of transport services; efficiency of organizational procedures; the latest high-tech and functional technologies; public support or significant private investment. The development and implementation of existing mechanisms and methods for the efficient management of transport and logistics centers in Ukraine can provide significant competitive advantages to the transport sector and the country’s economy as a whole, which is a promising area for further scientific and practical research.